Monoamine Oxidase Inhibition by Kavalactones from Kava (Piper Methysticum) - Prinsloo, Denise; van Dyk, Sandra; Petzer, Anél; Petzer, Jacobus P. (Planta Medica, 2019)
Monoamine oxidases (MAOs) are key metabolic enzymes for neurotransmitter and dietary amines and are targets for the treatment of neuropsychiatric and neurodegenerative disorders. This study examined the MAO inhibition potential of kavain and other kavalactones from the roots of kava (Piper methysticum), a plant that has been used for its anxiolytic properties. (±)-Kavain was found to be a good potency in vitro inhibitor of human MAO-B with an IC50 of 5.34 µM. (±)-Kavain is a weaker MAO-A inhibitor with an IC50 of 19.0 µM. Under the same experimental conditions, the reference MAO inhibitor, curcumin, displays IC50 values of 5.01 µM and 2.55 µM for the inhibition of MAO-A and MAO-B, respectively. It was further established that (±)-kavain interacts reversibly and competitively with MAO-A and MAO-B with enzyme-inhibitor dissociation constants (Ki) of 7.72 and 5.10 µM, respectively. Curcumin in turn, displays a Ki value of 3.08 µM for the inhibition of MAO-A. Based on these findings, other kavalactones (dihydrokavain, methysticin, dihydromethysticin, yangonin, and desmethoxyyangonin) were also evaluated as MAO inhibitors in this study. Yangonin proved to be the most potent MAO inhibitor with IC50 values of 1.29 and 0.085 µM for MAO-A and MAO-B, respectively. It may be concluded that some of the central effects (e.g., anxiolytic) of kava may be mediated by MAO inhibition.
Keywords: monoamine oxidase; inhibition; kava; Piper methysticum; Piperaceae; kavain; yangonin